Analyzing research methodologies and publication trends in service marketing literature - Mehvish Umer; Shama Razi (Cogent Business & Management, 2018)
Purpose: This paper explores the key trends in publications and research methodologies used in Service marketing literature across geographical regions during the past 28 years. Examining academic content over a selected time period presents valuable insights into how service marketing has evolved and approached to maturity. Design/methodology/approach: This paper is based on literature review of the published papers during the time period (1974–2014) in academic journals. A total of 153 relevant papers were analyzed excluding book reviews, conference papers. The paper analyzed firstly, research methodologies developments in terms of data collection, research design, sample size, sampling technique, statistical technique, respondent type, response rate, and time horizon used in different studies. Secondly, authorship type, authorship collaboration, top journal and journals rating in terms of publication trends. Descriptive statistics provide an overview of the research contribution in this specific time domain for service marketing. Findings: The main finding during the 28-year period analysis discloses that there is an inclining importance to research in Europe and other regions of the world than in North America. Other findings include a trend towards co-authorship, the preference to use of surveys over experiments and rising trend incorporating reliability and validity measures, factor analysis, structural equation modeling, and analysis of variance as the most popular statistical techniques. Research limitation: This study focuses on the methodological and publication trends analysis based on 153 research papers published in scholarly journals. One of the limitations of our study is the number of papers reviewed..
Keywords: 650